24 Exercise capacity improvement in adult congenital heart disease patients switching from bosentan to macitentan therapy. (2nd February 2018) - Herbert, S; Harries, C; Barbosa, J; Tulloh, R; Kempny, A; McCabe, C; Wort, J; Dimopoulos, K; Price, Laura
Abstract : Purpose: Therapeutic options for patients with congenital heart disease (PAH-CHD) are limited. Endothelin receptor antagonists do play a role, 1 however the recent MAESTRO trial showed that Macitentan only improved six-minute walk distance (6 MWD) in the control group. 2 We report real world use of patients who switch from Bosentan to Macitentan in a single centre PAH-CHD cohort. Methods: Clinical data was collected retrospectively from September 2014 to April 2017, up to 12 months after Macitentan introduction. Non-parametric statistical tests were used. Results: 16 PAH-CHD patients (13 female, age 52±10 years) were followed for 9.4 (0.7–25.9) months. All but 3 (19%) tolerated the change in medication, with no significant adverse events. At three months, exercise capacity improved in the patients where paired 6 MW tests were available (n=6: mean 6 MW 261±159 m at baseline to 415±84 m at 3 months, p=0.05), but this was not maintained at later time points. There was no significant change in WHO FC. Oxygen saturations improved at 3 months (87±7 vs 91±8, p=0.3), but saturations post-exercise failed to improve. BNP fell at the 3 and 6 month assessment (from 223 to 163 ng/L, then to 181 ng/L at 6 months, p=0.4, p=0.7) but this was not sustained at 12 months (figure 1). Echocardiographic measurements including TAPSE showed a non-significant improvement from baseline to 6 to 9 months and a decline thereafter, in line with the BNP findings (figure 2). Conclusion: Exercise capacity, BNP and TAPSE improved after 3 months in some patients with PAH-CHD, but this was not sustained beyond 6 months. References: . Nazzareno G, Marc H, Jean-Luc V, Simon G, et al. 2015ESC/ERS guidelines for the diagnosis and treatment of pulmonary hypertension: The joint task force for the diagnosis and treatment of pulmonary hypertension of the European Society of Cardiology (ESC) and the European Respiratory Society (ERS). Eur Heart J 2016;37(1):67–119. doi:10.1093/eurheartj/ehv317 . Galiè N. Actelion announces results of the MAESTRO study with Macitentan in patients with pulmonary arterial hypertension due to eisenmenger syndrome . https://www1.actelion.com/en/our-company/news-and-events.page?newsId=2072728 [Accessed: May 2017].